Weapons [videorecording (Blu-Ray)] - Cregger, Zach, 1981-; Brolin, Josh; Garner, Julia, 1994-; Ehrenreich, Alden, 1989- (Warner Bros., 2025)
When all but one child from the same class mysteriously vanish on the same night at exactly the same time, a community is left questioning who or what is behind their disappearance.